Contrasting Along-Slope vs. Downslope Sedimentation Style on the High-Latitude Eastern Canadian Continental Margin During the Last 40 ka - Rashid, Harunur; He, Jianing; Patro, Ranjan; Brown, A. Owen (Frontiers in Earth Science, 2022)
Late Pleistocene Labrador Sea depositional systems developed in front of ice streams and glacier outlets from the Laurentide Ice Sheet (LIS) are documented by Huntec and 3.5 kHz seismic profiles and piston cores. Due to efficient grinding by the LIS, massive amounts of fine-grained sediments and meltwater were delivered to the neighboring Labrador Sea during the periodic expansion and contraction tied to the Heinrich events (H-events) of the last glaciation. Depending on the position of the Hudson Strait ice stream, fine-grained sediments and meltwater were directly delivered on the lower shelf and upper slope, which were transported southward by the Labrador Current and western boundary current; or on the upper to lower Labrador slope, which were transported by the Northwest Atlantic Mid-Ocean Channel to distal sites. Nepheloid-flow layer at or near the sea bottom or at mid-water depths develop from meltwater loaded with an excessive charge of fine-grained sediments. Contrastingly, non-discriminatory ice rafting process delivered detritus of all sizes, but its total contribution to the sediment column is only minor, notwithstanding its paleoclimatic significance during H-events. Heinrich H1, H2, and H4 layers were identified by their characteristic nepheloid-flow layer deposits, i.e., alternating coarse silt and clay-sized laminae with thin ice-rafted debris interspersed by coarse to fine-grained dropstone. Further, the progressive thinning and eventual disappearance of the fine-laminae (i.e., coarse and fine silt/clay) in H-layers at the distal sites suggests the exhaustion and raining out of fines due to long-distance transport. However, the H3 layer was identified by a combination of nepheloid-flow layer deposits and finely-laminated mud turbidites at proximal sites. In the lower Labrador Slope and Basin, the H3 stratigraphic equivalent layer was identified by exorbitantly thick finely-laminated carbonate-rich mud turbidites. The divergent sedimentation style (i.e., reflected by the sediment facies) and the thickness of the H3 layer compared to other H-events suggests that the Hudson Strait ice-stream position was different compared to other H-events. Therefore, our data imply that the divergence in the H3 layer between the eastern and western North Atlantic might lie with the position of the Hudson Strait ice stream on the Labrador continental margin.